2012
DOI: 10.3340/jkns.2012.52.2.80
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of the Prognostic Factors in Ruptured Middle Cerebral Artery Aneurysm with Intracerebral Hemorrhage

Abstract: ObjectiveThis study analyzed the relationship between prognosis and multiple clinical factors of ruptured middle cerebral artery (MCA) aneurysm with intracerebral hemorrhage (ICH), to aid in predicting the results of surgical treatment.MethodsEnrolled subjects were 41 patients with ruptured MCA aneurysm with ICH who were treated with surgical clipping. Clinical factors such as gender, age, and initial Glasgow coma scale were assessed while radiological factors such as the volume and location of hematoma, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…Aneurysmal SAH accompanied by ICH is associated with poor functional outcome. 4 , 7–11 The rate of unfavorable outcomes in our study was 44.8%, which is in accordance with the range of 21.4% to 76.2% as reported in previous studies. 1 , 2 , 5 , 7 , 10 , 14 , 16–19 The poor initial clinical conditions, age, occurrence of spontaneous infarction, symptomatic vasospasm, ICH volume, aneurysm size, and midline shift are predictors of prognosis in patients with ICH secondary to aneurysms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Aneurysmal SAH accompanied by ICH is associated with poor functional outcome. 4 , 7–11 The rate of unfavorable outcomes in our study was 44.8%, which is in accordance with the range of 21.4% to 76.2% as reported in previous studies. 1 , 2 , 5 , 7 , 10 , 14 , 16–19 The poor initial clinical conditions, age, occurrence of spontaneous infarction, symptomatic vasospasm, ICH volume, aneurysm size, and midline shift are predictors of prognosis in patients with ICH secondary to aneurysms.…”
Section: Discussionsupporting
confidence: 92%
“… 1 , 2 , 5 , 7 , 10 , 14 , 16–19 The poor initial clinical conditions, age, occurrence of spontaneous infarction, symptomatic vasospasm, ICH volume, aneurysm size, and midline shift are predictors of prognosis in patients with ICH secondary to aneurysms. 1 , 5 , 7 , 18 The clot evacuation is considered an important predictor of prognosis in ruptured MCA aneurysms concomitant with ICH, especially in large hematomas. 14 , 15 However, the volume of ICH secondary to ruptured AcomA aneurysms is smaller than that of MCA aneurysms, which results in lesser occupying effect.…”
Section: Discussionmentioning
confidence: 99%
“…Volume pendarahan intraserebral pada penelitian ini dikelompokkan berdasarkan perjalanan klinis penyakitnya menjadi volume diatas 31 ml dan dibawah 31 ml. Digunakan nilai cut-off 31 ml karena pada batas jumlah volume pendarahan 31 ml, ditemukan hasil nilai spesifisitas dan sensitivitas tertinggi untuk hubungan antara volume pendarahan intraserebral dengan prognosis penyakit, yang berarti perbedaan presentase pasien dengan outcome klinis baik dan pasien dengan outcome klinis buruk paling besar pada nilai cut-off 31 ml (Oh, et al, 2012) (Grysiewicz, et al, 2008).…”
Section: Materi Dan Metode Penelitianunclassified
“…Prat et al9) categorized hematomas into temporal ICH and ISH, and observed better outcomes in patients with temporal. Oh et al7) grouped hematomas into frontal ICH, temporal ICH, and ISH, and found that temporal ICH had more favorable clinical outcome when compared to the other hematoma groups.…”
Section: Discussionmentioning
confidence: 99%